229k views
3 votes
3(x+1)+11 = -2(x+13)
Thank you for the help

2 Answers

3 votes

Answer:

x = -8

Explanation:

3(x+1)+11=-2(x+13)

3x+3+11=-2x-26

3x+14=-2x-26

5x=-40

x=-8

User Fabrice
by
5.5k points
1 vote

Answer:

x = -8

Explanation:

Step 1: Write equation

3(x + 1) + 11 = -2(x + 13)

Step 2: Solve for x

  1. Distribute: 3x + 3 + 11 = -2x - 26
  2. Combine like terms: 3x + 14 = -2x - 26
  3. Add 2x to both sides: 5x + 14 = -26
  4. Subtract 14 on both sides: 5x = -40
  5. Divide both sides by 5: x = -8

Step 3: Check

Plug in x to verify it's a solution.

3(-8 + 1) + 11 = -2(-8 + 13)

3(-7) + 11 = -2(5)

-21 + 11 = -10

-10 = -10

User Mibm
by
5.9k points